Optimizing performance of fuzzy decision support system with multiple parameter dependency for cloud provider evaluation - Rani, Uma; Dalal, Surjeet; Kumar, Jugnesh (International Journal of Engineering and Technology, 2017)
In today’s world, technological trend offers computing resources as services through the internet in on-demand or pay-as-you-go approach. These services are provided by different cloud service providers. Due to which trust on the any service provider is a choice of any customer. In order to choose a reputed cloud service provider a new method using the concept of fuzzy has proposed in this paper. This method enhanced the customer’s satisfaction level of using cloud services by avoiding ambiguities in fuzzy interface system (FIS) through optimization.Proposed fuzzy rule-based decision support system is collaborating with advanced fuzzy system optimized using a swarm intelligent firefly algorithm that facilitates the consumers in selecting right CSP based upon their rating value. It conducts three different reviews of three different components, i.e. customer review, service provider review and public review. Results are carried out on the basis of both simple and the optimized fuzzy, and it is found that the optimized fuzzy surpasses the simple fuzzy logic.